2012
DOI: 10.1158/0008-5472.can-11-0188
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity and Prognostic Significance of Growth Differentiation Factor GDF15 Secreted by Bone Marrow Mesenchymal Stem Cells in Multiple Myeloma

Abstract: Overexpression of growth differentiation factor 15 (GDF15) by bone marrow mesenchymal stem cells occurs widely in patients with multiple myeloma, but the pathophysiologic effects of GDF15 in this setting remain undefined. GDF15 has been described in numerous solid tumors but never in hematologic malignancies. In this study, we report that GDF15 significantly increases survival of stroma-dependent multiple myeloma cells including primary multiple myeloma cells. In particular, GDF15 conferred resistance to melph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
87
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 47 publications
(65 reference statements)
15
87
0
2
Order By: Relevance
“…33 Recent studies suggest that GDF15 might be involved in the growth, survival, and invasiveness of various cancers. 19,20,34 In the present study, human PBMo-derived macrophages stimulated with TECM acquired M2-like characteristics and upregulated GDF15 in vitro. Several previous studies also showed that PBMo-derived macrophages acquired M2 characteristics such as CD163, CD204, IL-10, VEGFA, and MMPs by conditioned medium of tumor cell line (TCM).…”
Section: Gdf15 Increased the Growth Of The Escc Cell Lines By Triggersupporting
confidence: 52%
See 2 more Smart Citations
“…33 Recent studies suggest that GDF15 might be involved in the growth, survival, and invasiveness of various cancers. 19,20,34 In the present study, human PBMo-derived macrophages stimulated with TECM acquired M2-like characteristics and upregulated GDF15 in vitro. Several previous studies also showed that PBMo-derived macrophages acquired M2 characteristics such as CD163, CD204, IL-10, VEGFA, and MMPs by conditioned medium of tumor cell line (TCM).…”
Section: Gdf15 Increased the Growth Of The Escc Cell Lines By Triggersupporting
confidence: 52%
“…Among the 12 genes related to tumor development (upregulated, seven genes including IL-6, IL-8, and CXCL1; downregulated, five genes; Table 1), we decided to focus on the GDF15 gene transcript (GDB accession no. NM_004864) that showed a log2 ratio of ∼ 4.0 in each cell line because TAM-derived GDF15, which is known to be a divergent member of human TGF-β superfamily associated with the growth and invasiveness of various cancers, 19,20 had not yet been reported in the microenvironment of ESCC.…”
Section: Upregulation Of Gdf15 Expression In Pbmo-derived Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although NAG-1 is involved in acute stress-induced apoptotic process (10), increasing recent evidences demonstrated that NAG-1 can trigger homeostatic cellular responses and play protective roles in both physiological and pathological states, including chronic inflammation and tumorigenesis (16)(17)(18)(19). In response to the cytotoxic NSAIDs, cells also can produce the survival signals.…”
Section: Discussionmentioning
confidence: 99%
“…Although most intestinal epithelial cells maintain a low level of NAG-1 expression, apoptotic mucosal surface epithelial cells can have relatively high levels of NAG-1 (15). Although NAG-1 is involved in acute stress-induced apoptotic process (10), increasing recent evidences demonstrated that NAG-1 can trigger homeostatic cellular responses and play protective roles in both physiological and pathological states, including chronic inflammation and tumorigenesis (16)(17)(18)(19). NAG-1, one of the major secreted proteins induced by p53, is thought to be important for promoting p53-mediated activity associated with cell cycle arrest and apoptosis (20).…”
mentioning
confidence: 99%